Urinary bladder-containing incarcerated inguinoscrotal hernia: a case report. Issue 11 (25th November 2020) - Karanikas, Michael; Kofina, Konstantinia; Foutzitzi, Soultana; Deftereos, Savas; Effraemidou, Eleni; Lyratzopoulos, Nikolaos; Polychronidis, Alexandros
Abstract: Inguinoscrotal hernia containing the urinary bladder is a rare entity found in 1–4% of inguinal hernias, while patients rarely present symptoms of urinary dysfunction. We present the case of a 79-year-old Caucasian male with acute renal dysfunction and incarcerated inguinoscrotal hernia containing the entire urinary bladder. The patient presented in the surgical emergency department due to an incarcerated right inguinoscrotal hernia and deteriorated renal function. Preoperatively, ultrasound imaging was performed, which showed the presence of the whole bladder in the hernia sac. The bladder was repositioned to its anatomic position and hernia was repaired through a modified Lichtenstein technique. In patients with inguinoscrotal hernia and acute urinary tract symptoms, surgeons should be aware of the possibility of inguinal bladder hernia. Preoperative imaging can help in preventing intraoperative bladder damage.